Qualidade das instituições: estimação de indicadores agregados, de seus determinantes e de seus efeitos sobre a renda per capita - Jose Ronaldo de Castro Souza Junior (2013)
The discussion on the importance of institutions in determining the level of economic development of countries has come to prominence in recent decades; nevertheless there are still important issues to be analyzed. This dissertation aims to contribute to the literature by developing new aggregate indicators of institutions, estimating the determinants of economic institutions, and using an econometric approach that is not the standard in this literature to analyze both the direct effects of economic institutions, political institutions and education on income per capita.Firstly, it was estimated new aggregate indicators that allowed capturing the various dimensions of the theoretical concepts of political institutions and economic institutions. Special attention was given to the quality of the sources of primary data disaggregated and the choice of statistical method of aggregation. The sample was as large as possible in terms of both the number of countries and the temporal scope of the data, without having to compromise the quality of the estimates.Further, we analyzed empirically the determinants of economic institutions themselves. The econometric results indicate clearly that the political institutions and the durability of the political regime positively affect economic institutions. Furthermore, the improvement of education can also help improve economic institutions and the effect of regime durability seems to be higher in autocracies.The results of the last chapter, in turn, indicate that economic institutions have significant and positive effects on per capita income. However, the positive effects of education were not significant in several of the models estimated and the direct effects of political institutions on per capita income showed to be negative. Still, political institutions may have indirect positive effects on income through its influence on the determination of economic institutions.